2015
DOI: 10.1001/jamasurg.2014.3484
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incident Hemodialysis Access and Mortality

Abstract: Current incident AVF practice falls exceedingly short years after recommendations were made in 1997. The impact of this shortcoming on mortality for patients with end-stage renal disease is enormous. Functioning permanent access at initiation of HD confers lower mortality even compared with patients temporized with an HC while awaiting maturation of permanent access. A change of current policies and structured multidisciplinary efforts are required to establish matured fistulae prior to HD to ameliorate this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(86 citation statements)
references
References 33 publications
1
84
0
1
Order By: Relevance
“…Gillespie et al [16] found that pre-ESRD nephrology care for >12 months was significantly associated with initial AVF or graft use vs. catheter (aOR 11.3). Further, Chan et al [3] observed a 61% reduction in early death risk in those patients who initiated dialysis with an AVF, consistent with many studies demonstrating lower morbidity and mortality associated with AVF vs. catheter use [18,19,20,21,22,23,24,25,38,39]. In our study, the likelihood of catheter use at dialysis initiation was reduced by 67% among MHS vs. non-MHS patients, which could partly explain the improved survival in the MHS cohort, given the attenuation of its survival advantage after adjusting for vascular access types in the regression model.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Gillespie et al [16] found that pre-ESRD nephrology care for >12 months was significantly associated with initial AVF or graft use vs. catheter (aOR 11.3). Further, Chan et al [3] observed a 61% reduction in early death risk in those patients who initiated dialysis with an AVF, consistent with many studies demonstrating lower morbidity and mortality associated with AVF vs. catheter use [18,19,20,21,22,23,24,25,38,39]. In our study, the likelihood of catheter use at dialysis initiation was reduced by 67% among MHS vs. non-MHS patients, which could partly explain the improved survival in the MHS cohort, given the attenuation of its survival advantage after adjusting for vascular access types in the regression model.…”
Section: Discussionmentioning
confidence: 57%
“…One of the primary focuses of pre-ESRD care is the creation of an arteriovenous fistula (AVF), as recommended by the Kidney Disease Improving Global Outcomes to be the vascular access of choice for patients needing maintenance HD [17] due to its longevity and lower rates of infection and intervention. Many studies demonstrate that HD using an AVF is associated with improved survival and fewer hospitalizations compared with the complication-prone dialysis catheters [18,19,20,21,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Ideally, swift transitions from use of a TCVC to an AVA would occur, such that chronic TCVC use (>3 months in the absence of a maturing AVA) would occur in <10% of prevalent patients [5]. Due to the frequent absence of pre-dialysis access preparation, advanced comorbidities, patient preference, acute illnesses, and other factors, this is an unmet goal; more than 60% of incident ESKD patients on HD continue to use a TCVC for more than 90 days [6]. For those who switch from using a TCVC to using an AVA, the dynamics of vascular access conversion extend beyond a one-time transition phase and few longitudinal studies assessed the aspects of interchanging accesses and sequence of AVA placement.…”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover a higher proportion of patients initiate haemodialysis with a central venous catheter (CVC) in the USA (82.6%) than in any other country for which data are available. 3 Using a database of >500,000 US patients who initiated haemo dialysis between 2006 and 2010, Malas et al analy sed the trends in incident vascular access use and the impact of type of incident vascular access on patient survival. 3 They identified a marginal increase in the use of AVFs for incident vascular access from 12.2% in 2006 to 15.0% in 2010; CVC use remained consistently high (82.5%) during the study period.…”
mentioning
confidence: 99%
“…3 Using a database of >500,000 US patients who initiated haemo dialysis between 2006 and 2010, Malas et al analy sed the trends in incident vascular access use and the impact of type of incident vascular access on patient survival. 3 They identified a marginal increase in the use of AVFs for incident vascular access from 12.2% in 2006 to 15.0% in 2010; CVC use remained consistently high (82.5%) during the study period. Importantly, adjusted mortality was 35% lower in those using an AVF and 18% lower in those using an arteriovenous graft (AVG) for incident haemodialysis than in those using a CVC.…”
mentioning
confidence: 99%